Inflammatory Foreign Body Response Induced by Neuro-Implants in Rat Cortices Depleted of Resident Microglia by a CSF1R Inhibitor and Its Implications - Sharon, Aviv; Jankowski, Maciej M.; Shmoel, Nava; Erez, Hadas; Spira, Micha E. (Frontiers in Neuroscience, 2021)
Inflammatory encapsulation of implanted cortical-neuro-probes (the foreign body response-FBR) severely limits their use in basic brain research and in clinical applications. A better understanding of the inflammatory FBR is needed to effectively mitigate these critical limitations. Combining the use of the brain permeant colony stimulating factor 1 receptor inhibitor PLX5622, and a Perforated Polyimide-based Multielectrode array Platform (PPMP) that can be sectioned along with the surrounding tissue, we examined the contribution of microglia to the formation of inflammatory FBR. To that end, we imaged the inflammatory processes induced by PPMP implantations after eliminating 89%-94% of the cortical microglia by PLX5622 treatment. The observations showed that: (I) inflammatory encapsulation of implanted PPMPs proceeds by astrocytes in 89%-94% of the microglia-free cortices. The activated astrocytes adhered to the PPMP’s surfaces. This suggests that the roles of microglia in the FBR might be redundant. (II) PPMP implantation into control, or continuously treated rats by PLX5622 triggered a localized surge of microglia mitosis. The daughter cells that formed a “cloud” of short-lived (T1/2 ≤ 14 days) microglia around and in contact with the implant surfaces were PLX5622-insensitive. (III) Neuron degeneration by PPMP implantation and the ensuing recovery in time, space and density progress in a similar manner in the cortices 89%-94% depleted of microglia. This implies that microglia do not serve a protective role with respect to the neurons. (IV) Although the overall cell composition and dimensions of the encapsulating scar in PLX5622 treated rats differed from the controls, the recorded FPs qualities and yield were undistinguishable. This is accounted for by assuming that the FP amplitudes in the control and PLX5622 treated rats were related to the seal resistance formed at the interface between the adhering microglia and/or astrocytes and the PPMP platform rather than across the scar tissue. These observations suggest that the prevention of both astrocytes and microglia adhesion to the electrodes is required to improve FP recording quality and yield.